Incidence of Mild Traumatic Brain Injury: A Prospective Hospital, Emergency Room and General Practitioner-Based Study - Skandsen, Toril; Nilsen, Tom Lund; Einarsen, Cathrine; Normann, Ingunn; McDonagh, David; Haberg, Asta Kristine; Vik, Anne (Frontiers in Neurology, 2019)
Background There are no recent estimates of incidence rates of mild traumatic brain injury (MTBI) from Norway. Moreover, reported incidence rates rarely comprise cases of MTBI evaluated in the primary care setting. In this study, we utilized existing data collected as part of the recruitment to a large, follow-up study of patients with MTBI. We estimated the incidence rate of MTBI, including patients who visited outpatient clinics, in the age group 16-59 years in a Norwegian region. Methods: During 81 weeks in 2014 and 2015, all persons aged 16-59 years, presenting with possible MTBI to the emergency department (ED) at St. Olavs Hospital, Trondheim University Hospital or to the general practitioner (GP)-run Trondheim municipal outpatient ED, were evaluated for a diagnosis of MTBI. Patients were identified by computerized tomography (CT) referrals and patient lists. Patients referred to acute CT from their primary GP with suspicion of MTBI were also recorded. This approach identified 732 patients with MTBI. Age- and sex-specific incidence rates of MTBI were calculated using population figures from the regional catchment area. Results: Overall incidence of MTBI in people between 16-59 years was 302 per 100,000 person-years (95% confidence interval 281-324). The incidence rate was highest in the age group 16-20 years, where rates were 835 per 100,000 person-years in males and 726 in females. Conclusion: The overall incidence rate of MTBI was low compared to studies conducted in non-Nordic countries. Like other reports, the incidence was highest in the late teens.